Taxonomic characterization and GC-MS analysis of two edible mushrooms - Musale, Ganesh P.; Kakde, Rajendra (Mushroom Research, 2025)
Mushroom specimens were collected during August 2024 from Mantha tahsil of Jalna district of Maharashtra. Based on taxonomic characterization, the specimens were identified as Calocybe indica Purkay & A. Chandra and Volvariella volvocea (Bull.) Singer. For analysis of their biochemical analysis, methanolic extract were prepared and Gas Chromatography-Mass Spectrometry (GC-MS)analysis showed the presence of biotic compounds such as Dimethyl sulfide, Dodecane, Tetradecane, Diethyl Phthalate, Tetradecanal, 2-Pentadecanone, Pentadecanal, 1-Nonadecene, 2-Nonadecanone, Methyl 13-methyltetradecanoate, 7-Hexadecenal, (Z)-Hexadecanoic acid, methyl ester, Hexadecanoic acid, 15-methyl-, methyl ester, 9-Octadecenoic acid, methyl ester, (E)- 2(3H)-Furanone, 5-dodecyldihydro-, Hexadecanoic acid, pentyl ester, etc in both mushrooms. The identified compounds reportedly show diverse bioactivities such as insecticide, antiviral, anticancer, antimicrobial, antioxidant, antitubercular hypocholesterolemic, anti-inflammatory and antiandrogenic. The presented results may provide baseline information about bioactive constituents of above-mentioned mushrooms in providing valuable compounds for medicinal and agricultural importance.